Error analysis and kinematic calibration of a new 3-PRS parallel mechanism. (September 2020) - Sun, Fuwei; Chen, Guoqiang; Chen, Shuisheng; Li, Yongsheng; Yuan, Jingshuai; Zhang, Qin
Abstract: Taking a new 3-PRS parallel mechanism as the research object, error analysis and kinematics calibration are carried out. Combining with inverse kinematics, the parameter error of the mechanism is analyzed comprehensively. a calibration method of inverse kinematics based on structural parameters and genetic algorithm is proposed, and the error calibration model of 3-PRS parallel mechanism is deduced. The calculation by MATLAB shows that the reverse motion error calculated by nominal machine tool structural parameters is larger than that obtained by calibrated structural parameters. The position of the three cylindrical and spherical hinges after calibration is closer to the nominal position. It shows that the error calibration can correct the machine tool structure and guide the subsequent installation and debugging of the machine tool.